2017
DOI: 10.1002/2017gl073236
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of Antarctic maximum sea ice extent by upper ocean stratification on a seasonal timescale

Abstract: This study uses an observationally constrained and dynamically consistent ocean and sea ice state estimate. The author presents a remarkable agreement between the location of the edge of Antarctic maximum sea ice extent, reached in September, and the narrow transition band for the upper ocean (0–100 m depths) stratification, as early as April to June. To the south of this edge, the upper ocean has high stratification, which forbids convective fluxes to cross through; consequently, the ocean heat loss to the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
(90 reference statements)
0
6
0
1
Order By: Relevance
“…There are several reasons why coastal regions near Greenland and Labrador such as Baffin Bay, Fylla Bank, and W of CB would be more prone to sea ice than a mid‐ocean site like E of CB: clearly more northerly regions would have colder temperatures and coastal regions would generally be more sheltered, allowing ocean surface stratification which is conducive to sea ice formation (Su, ). Additionally, ocean surface regions close to the Greenland shelf are likely to have much lower salinities than the open sea due to efflux of ice and water from the ice cap in summer and marine glaciers in autumn and this would make sea ice formation more likely as temperatures drop below zero.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons why coastal regions near Greenland and Labrador such as Baffin Bay, Fylla Bank, and W of CB would be more prone to sea ice than a mid‐ocean site like E of CB: clearly more northerly regions would have colder temperatures and coastal regions would generally be more sheltered, allowing ocean surface stratification which is conducive to sea ice formation (Su, ). Additionally, ocean surface regions close to the Greenland shelf are likely to have much lower salinities than the open sea due to efflux of ice and water from the ice cap in summer and marine glaciers in autumn and this would make sea ice formation more likely as temperatures drop below zero.…”
Section: Discussionmentioning
confidence: 99%
“…ECCO has been used in many previous studies, both globally and in the Southern Ocean, and has been shown to be consistent with available observations (Boland et al., 2021; ECCO Consortium, 2017a, 2017b; Forget, Campin, et al., 2015; Fukumori et al., 2017). While a range of observational data sets covering different time periods are used to constrain sea ice in ECCO, leading to variations from any particular set of observations, mean September sea ice in ECCO has been validated against satellite data previously by Su (2017). Sea ice area in the regions focused on in this study was compared against the same satellite data (Meier et al., 2021), and shown to have very similar seasonal and interannual variability with an r 2 value of at least 0.7 for each model (Figure S1, https://nsidc.org/data/g02202/versions/4).…”
Section: Methodsmentioning
confidence: 99%
“…а -latitude of Т max (1) and Antarctic polar front (2); б -the same after smoothing with three years window; в -latitude of Т max (1) and sea ice extent (2); г -the same after smoothing with three years window . R is the correlation coefficient between (1) and (2) .…”
Section: выводыmentioning
confidence: 99%
“…Антарктический морской ледяной покров в период максимального развития ограничен с севера Антарктическим циркумполярным те чением и Антарктическим полярным фрон том (АПФ) и, следовательно, находится под влиянием факторов, определяющих его поло жение и интенсивность . Согласованность между максимальным распространением антарктиче ского морского льда в сентябре и положени ем переходной зоны в стратификации верхнего 100метрового слоя показана в работе [1] . При чина -разная стратификация верхнего слоя по обе стороны от переходной зоны .…”
Section: Introductionunclassified
See 1 more Smart Citation